KETERPENJARAAN TOKOH PEREMPUAN DALAM CERPEN THE YELLOW WALLPAPER KARYA CHARLOTTE PERKINS GILMAN - Asmarani, Ratna (Faculty of Humanities, Diponegoro University, 2015)
The purpose of this paper is to analyse the problems around the imprisonment of the female protagonist in Chalotte Perkins Gilmanâ€™s short story entiled The Yellow Wallpaper. The focus of the analysis is on the actors and factors causing imprisonment, types dan impacts of imprisonment, efforts to overcome the imprisonment, and the end of the imprisonment experienced by the female protagonist. To analyse this problems, feminist literary criticism is used supported by the stereotypes of the nineteenth century women, the medical opinion at that time and the feminist perspective concerning the mental disorder experienced by women, and the concept of oppression in the imprisonment as well. The result shows that a woman who experiences the physical and psychological imprisonment in the patriarchal household area tends to have mental disorder as an alternative to gain freedom. The conclusion that can be drawn is that in the patriarchal environment womenâ€™s movement area and psychological, emotional, intellectual actualizationÂ tend to be limited in which the women who fight against those linitations will get the stigma of suffering from mental illness.